Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
x=-4y+4
Therefore:
3(-4y+4)-7y=-7
-12y+12-7y=-7
12+7=7y+12y
19=19y
Therefore y=1.
When y=1,
x=-4(1)+4=-4+4=0.
Therefore:
3(-4y+4)-7y=-7
-12y+12-7y=-7
12+7=7y+12y
19=19y
Therefore y=1.
When y=1,
x=-4(1)+4=-4+4=0.
You have the (X) in a single substitute the equation of the second equation. Then, in an expression have the same (Y). Is a linear equation that that is easily solved. After finding the back of the basis of the expression at the beginning.
[tex]\begin{cases}x=-4y+4\\3x-7y=-7\end{cases}[/tex]
[tex]\begin{cases}x=-4y+4\\3(-4y+4)-7y=-7\end{cases}[/tex]
[tex]\begin{cases}x=-4y+4\\-12y+12-7y=-7\end{cases}[/tex]
[tex]\begin{cases}x=-4y+4\\-19y=-19|:(-19)\end{cases}[/tex]
[tex]\begin{cases}x=-4*1+4\\y=1\end{cases}[/tex]
[tex]\begin{cases}x=0\\y=1\end{cases}[/tex]
[tex]\begin{cases}x=-4y+4\\3x-7y=-7\end{cases}[/tex]
[tex]\begin{cases}x=-4y+4\\3(-4y+4)-7y=-7\end{cases}[/tex]
[tex]\begin{cases}x=-4y+4\\-12y+12-7y=-7\end{cases}[/tex]
[tex]\begin{cases}x=-4y+4\\-19y=-19|:(-19)\end{cases}[/tex]
[tex]\begin{cases}x=-4*1+4\\y=1\end{cases}[/tex]
[tex]\begin{cases}x=0\\y=1\end{cases}[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.